2010
DOI: 10.2495/air100161
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of magnetic particulates in urban and industrial dusts

Abstract: Morphology and mineralogy and magnetic parameters were analysed in atmospheric dust samples collected in 7 cities of Upper Silesia region (South Poland). The study was carried on by means of EDS spectroscopy, SEM technique, X-ray diffraction and Mössbauer spectroscopy. Special attention was paid to the magnetic fraction of studied dusts that is a potential carrier trace elements emitted to the environment. To assess the total content of magnetic fraction in bulk dust samples, mass specific magnetic susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Iron (Fe 0 ) and maghemite, the main constituents of the adsorbent Fe–MM, are widely available in the earth’s atmosphere. 38,39 They have been classified as sustainable materials by different groups. 40,41 Dust particles are very often formed via the aggregation of such iron particles with clay materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron (Fe 0 ) and maghemite, the main constituents of the adsorbent Fe–MM, are widely available in the earth’s atmosphere. 38,39 They have been classified as sustainable materials by different groups. 40,41 Dust particles are very often formed via the aggregation of such iron particles with clay materials.…”
Section: Resultsmentioning
confidence: 99%
“…Iron (Fe 0 ) and maghemite, the main constituents of the adsorbent Fe–MM, are widely available in the earth’s atmosphere. , They have been classified as sustainable materials by different groups. , Dust particles are very often formed via the aggregation of such iron particles with clay materials . In this context, we investigated the effect of several environmentally available physicochemical conditions on the adsorption of BG on Fe–MM [Figure a].…”
Section: Resultsmentioning
confidence: 99%
“…Lung epithelial cells, treated with various concentrations of magnetic nanoparticles, showed that magnetite-treated cells induce oxidative stress, deplete antioxidant levels, and affect the apoptotic pathway [62]. Note the commonality: Iron oxide is a component of air pollution, CFA, and asbestos [56,63,64]; magnetite (Fe 3 O 4 ) is even found in cigarette smoke and ash [65].…”
Section: Pbmentioning
confidence: 99%
“…The magnetic characteristics of the atmospheric particulate matter is sometimes studied using dust fall samples (e.g. Liu et al, 2019;Magiera et al, 2010). The magnetic properties of particles deposited on biological surfaces can be useful in terms of the biomagnetic monitoring of atmospheric pollution (Hofman et al, 2017;Maher, 2009;Mejía-Echeverry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%